ANALISIS YURIDIS PERTIMBANGAN HUKUM HAKIM DALAM PUTUSAN PERKARA NOMOR 1394/Pdt.G/2020/PA.Cmi - NIM. A1011201230, RATU ANDANI PUTRI PRAMESHWARI (Jurnal Fatwa Hukum, 2024)
Abstract  Divorce is the final choice if the problems in the household are not resolved and can no longer be maintained, this is in line with Article 39 of Law Number 1 of 1974 concerning Marriage. The grounds for divorce are regulated in Article 19 of Government Regulation Number 9 of 1975 jo. Article 116 of the Compilation of Islamic Law. Divorce cases that occur in the Cimahi Religious Court where the defendant has a sexual orientation disorder become a new legal issue because it is not regulated in existing legal provisions. This type of research is a descriptive normative legal research. The type of data used in this research is secondary data. Data collection techniques used through literature studies in the form of books, journals, laws and regulations, documents such as case files. Data analysis uses the legal construction method of analogical thinking. Based on the results of research and data analysis that has been carried out, the judge's consideration has granted the plaintiff's claim by paying attention to the principles of legal certainty, the principles of justice and the principles of expediency. The legal consequences of this decision are the dissolution of marriage by imposing divorce one ba'in sughra Defendant against the Plaintiff, the division of joint property obtained during the marriage period and child custody.  Keywords: Judges' Legal Considerations, Decisions, Divorce, LGBT, Homosexuals    Abstrak  Perceraian menjadi pilihan akhir apabila permasalahan dalam rumah tangga tidak terselesaikan dan tidak dapat lagi dipertahankan, hal ini sejalan dengan Pasal 39 Undang-undang Nomor 1 Tahun 1974 tentang Perkawinan. Adapun yang menjadi alasan-alasan perceraian diatur dalam pasal 19 Peraturan Pemerintah Nomor 9 Tahun 1975 jo. Pasal 116 Kompilasi Hukum Islam. Perkara perceraian yang terjadi di Pengadilan Agama Cimahi dimana pihak tergugat memiliki kelainan orientasi seksual menjadi persoalan hukum baru karena tidak diatur dalam ketentuan hukum yang ada. Jenis penelitian ini merupakan penelitian hukum normatif yang bersifat deskriptif. Jenis data yang digunakan dalam penelitian ini adalah data sekunder. Teknik pengumpulan data yang digunakan melalui studi kepustakaan baik berupa buku-buku, jurnal, peraturan perundang-undangan, dokumen seperti berkas perkara. Analisis data menggunakan metode konstruksi hukum berfikir analogi. Berdasarkan hasil penelitian dan analisis data yang telah dilakukan bahwa pertimbangan hakim tersebut telah mengabulkan gugatan Penggugat dengan memperhatikan asas kepastian hukum, asas keadilan dan asas kemanfaatan. Akibat hukum dari putusan ini adalah putusnya perkawinan dengan menjatuhkan talak satu ba"™in sughra Tergugat terhadap Penggugat, pembagian harta bersama yang didapat selama masa perkawinan dan hak asuh anak.    Kata Kunci: Pertimbangan Hukum Hakim, Putusan, Cerai Gugat, LGBT, Homoseksual